Evaluation of the Safety of Deutetrabenazine at Higher Doses to Treat Chorea in Huntington's Disease. (April 2021) - Frank, Samuel; Vaughan, Christina; Stamler, David; Oakes, David; Davis, Mat D.; Gross, Nicholas; Gordon, Mark Forrest; Savola, Juha-Matti; Wieman, Maria; Eberly, Shirley; Kayson, Elise; Whaley, Jacquelyn; et al.
Abstract: Background: In the First-HD pivotal trial, the maximum deutetrabenazine dose evaluated to treat chorea associated with Huntington's disease (HD chorea) was 48 mg/d, which is the approved maximum dose for this population. In ARC-HD, an open-label extension study evaluating the long-term efficacy and safety of deutetrabenazine to treat HD chorea, dosage ranged from 6 mg/d to 72 mg/d, with doses ≥12 mg/d administered twice daily. Doses in ARC-HD were increased by 6 mg/d per week in a response-driven manner based on efficacy and tolerability until 48 mg/d (Week 8). At the investigator's discretion, further increases were permitted by 12 mg/d per week to a maximum of 72 mg/d. This post-hoc analysis evaluates the safety and tolerability of deutetrabenazine >48 mg/d compared to ≤48 mg/d to treat HD chorea in ARC-HD. Methods: Patient counts and safety assessments were attributed to patients when they received a dose of either ≤48 mg/d or >48 mg/d. For 9 selected adverse events (AEs), we compared AE rates adjusted for duration of drug exposure (as number of AEs/year) at ≤48 mg/d or >48 mg/d. The AE rates were determined after titration when participants were on stable doses of deutetrabenazine. Results: All 113 patients were exposed to doses ≤48 mg/d (177.1 patient-years) and 49 patients were ever exposed to doses >48 mg/d (74.1 patient-years). In patients taking deutetrabenazine >48 mg/d compared to ≤48 mg/d after the titration period, there were no apparent differences in exposure-adjusted AE rates. Conclusions: Based on clinical experience, some patients with HD may benefit from doses higher than 48 mg/d to adequately control chorea. These doses were tolerated without apparent increase in the exposure-adjusted rates of selected AEs after titration. This analysis does not address the occurrence of other AEs or whether adequate efficacy was achieved at lower doses, factors that may have influenced dose increases. Funding: Teva Pharmaceutical Industries Ltd., Petach Tikva, Israel